EXPLORING THE MEANING OF LIFE OF LATE ADOLESCENTS THROUGH THE MODIFICATION OF MICHAEL F. STEGER'S THEORY SCALE - Roehan, Muhammad Sani; Izzaty, Rita Eka; Herwin, Herwin (Counsenesia Indonesian Journal Of Guidance and Counseling, 2025)
The search for meaning in life among late adolescents is a crucial factor in their identity development, especially in the midst of social and emotional challenges. Although many studies have been conducted on the meaning of life, the limitations of existing instruments are unable to reflect the complexity of the meaning of life experience in late adolescents, so modifications are needed to address this need. This study aims to modify the meaning of life scale to better fit the context and experiences of adolescents. Using a quantitative approach, 116 active students aged 18-21 years from various universities in three provinces participated in this study. The instrument used was a modified meaning of life scale based on Michael F. Steger's theory, including two dimensions, namely the existence of meaning and the search for meaning. The results of the analysis showed that the modified scale not only had high validity and reliability, but also effectively captured the complexity of adolescents' life experiences. The findings provide important insights in understanding the dynamics of adolescents' meaning in life and open up opportunities for the development of intervention programs that are more relevant and based on their needs.